Urban Sufisme dan Remaja Milenial di Majelis Ta’lim dan Sholawat Qodamul Musthofa Kota Pekalongan - Lukman Hakim (Journal of Sufism and Psychotherapy, 2021)
The phenomenon of the spiritual excitement of urban communities, especially teenagers, is certainly a symptom of a prolonged crisis and moral decadence influenced by the lifestyle of some urban communities. Adolescents, who are generally overwhelmed by mental instability so that they are prone to wear and tear, need a spiritual touch to restore calm and balance to their shaky souls. This is a phenomenon of urban sufism which is marked by the emergence of majelis ta'lim and dhikr in urban areas, including in the city of Pekalongan. This study aims to determine the background of adolescents following and understanding the meaning of Sufism in Majelis Ta'lim and Sholawat Qodamul Musthofa in Pekalongan City. This type of research is a field case study with qualitative methods. The approach used in this research is the Sufism approach. Data collection techniques in this study using interview techniques and direct observation. All data were analyzed using descriptive analysis methods. The results showed that adolescents who are students in the Ta'lim Council and Sholawat Qodamul Musthofa consist of various background problems in life, they experience moral degradation and spiritual crises so they choose the path of Sufism in order to find peace of mind and improve their lives. Sufism or Sufism gives a lot of meaning to adolescents through the teachings and amaliyah of Sufism so that it becomes a way to lead a better life than before.